Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Moving politics: Emotion and ACT UP’s fight against AIDS - Gould, Deborah B. (University of Chicago Press, 2009)
In the late 1980s, after a decade spent engaged in more routine interest-group politics, thousands of lesbians and gay men responded to the AIDS crisis by defiantly and dramatically taking to the streets. But by the early 1990s, the organization they founded, ACT UP, was no more—even as the AIDS epidemic raged on. Weaving together interviews with activists, extensive research, and reflections on the author’s time as a member of the organization, Moving Politics is the first book to chronicle the rise and fall of ACT UP, highlighting a key factor in its trajectory: emotion. Surprisingly overlooked by many scholars of social movements, emotion, Gould argues, plays a fundamental role in political activism. From anger to hope, pride to shame, and solidarity to despair, feelings played a significant part in ACT UP’s provocative style of protest, which included raucous demonstrations, die-ins, and other kinds of street theater. Detailing the movement’s public triumphs and private setbacks, Moving Politics is the definitive account of ACT UP’s origin, development, and decline as well as a searching look at the role of emotion in contentious politics.
https://transreads.org/wp-content/uploads/2021/07/2021-07-15_60f0412da8a40_deborah-gould-moving-politics-emotion-and-act-ups-fight-against-aids.pdf
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amériques; discipline; identités LGBTQIA2+; militance; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions; états-unis

On affect and protest - Gould, Deborah (Political Emotions, 2010)
Keywords: discipline; histoire et politique; militance; mouvements sociaux; ressource en ligne; science politique; science politique et droit; thématiques; émotions